A married woman - Kapur, Manju (Faber and Faber, 2003)
Astha has everything an educated, middle-class Delhi woman could ask for - a dutiful loving husband, space for children and affluent surroundings. So why is she consumed with unease? She finds herself embarking on a powerfully physical relationship with a much younger woman, Pipee, the widow of a political activist. But with this extra-marital affair is Astha foolishly jeopardizing everything - or is she at last throwing off the fear and timidity instilled in her by her parents, her husband, her social class?